(International and regional alliances in the Arab region and the different positions (2011 - 2015 - Obeidat, Maysoun Mansour (Journal of Economic, Administrative and Legal Sciences, 2017)
This research dealt with a number of military alliances competing since (2011-2015) and until the present time in the yard of a number of politically and militarily troubled Arab countries, especially Syria and Iraq, which has been and still is formed in order to fight terrorism led "Isis" or the so-called Islamic State of Iraq and the Levant, until it became not possible to achieve peace and security in these countries without resorting to military solutions, and those solutions Saudi Arabia's announcement on the tongue and the defense minister, Prince Mohammed bin Selman in mid-December / December 2015, the formation of "Islamic military alliance," which met with Trahibba and Asaaaly Arab and international levels, and at the same time there have been question marks and sharp criticism of the alliance by Iran and multiple militias Shiite without taking into account the declared aim Alliance, a counterterrorism Arab-led Islamic common, especially since the burning areas in the Arab world is witnessing three forms of alliances military: Shiite militias, irregular forces, and regional alliances, all of which led to the formation of the Islamic military alliance phenomenon inevitable required by the conditions in the region and the continuation of the policies enacted by King Selman bin Abdul Aziz Al Saud, to take the reins in the region, opening the door for Riyadh to take its place as a regional power , where he no longer leads the Gulf or only went Arab political and military efforts, but also the Muslim world, has been the formation of the alliance came in the framework of international legitimacy, the Arab, Islamic and international acceptance. However, some believe that the call for the formation of a Sunni alliance makes the Gulf countries are fighting terrorism under the umbrella of the Alliance sectarian, as some felt that the initiative speed and sudden announcement of the alliance has confounded political and military circles, where the coalition is still in great need of marketing and needs more time to turn to the military forces of hunting terrorism wherever and fight him.
Keywords: Alliance; Isis; terrorism; militias; international legitimacy